Which Patients with Isolated Para-aortic Lymph Node Metastasis Will Truly Benefit from Extended Lymph Node Dissection for Colon Cancer? - Bae, Sung Uk (Cancer Res Treat, 2018)
PURPOSE: The prognosis of patientswith colon cancer and para-aortic lymph node metastasis (PALNM) is poor. We analyzed the prognostic factors of extramesenteric lymphadenectomy for colon cancer patients with isolated PALNM. MATERIALS AND METHODS: We retrospectively reviewed 49 patients with PALNM who underwent curative resection between October 1988 and December 2009. RESULTS: In univariate analyses, the 5-year overall survival (OS) and disease-free survival (DFS) rates were higher in patients with ≤ 7 positive para-aortic lymph node (PALN) (36.5% and 27.5%) than in those with > 7 PALN (14.3% and 14.3%; p=0.010 and p=0.027, respectively), and preoperative carcinoembryonic antigen (CEA) level > 5 was also correlated with a lower 5-year OS and DFS rate of 21.5% and 11.7% compared with those with CEA ≤ 5 (46.3% and 41.4%; p=0.122 and 0.039, respectively). Multivariate analysis found that the number of positive PALN (hazard ratio [HR], 3.291; 95% confidence interval [CI], 1.309 to 8.275; p=0.011) was an independent prognostic factor for OS and the number of positive PALN (HR, 2.484; 95% CI, 0.993 to 6.211; p=0.052) and preoperative CEA level (HR, 1.953; 95% CI, 0.940 to 4.057; p=0.073) were marginally independent prognostic factors for DFS. According to our prognostic model, the 5-year OS and DFS rate increased to 59.3% and 53.3%, respectively, in patients with ≤ 7 positive PALN and CEA level ≤ 5. CONCLUSION: PALN dissection might be beneficial in carefully selected patients with a low CEA level and less extensive PALNM.